2014
DOI: 10.1177/2156587214530720
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina maxima Protects Liver From Isoniazid and Rifampicin Drug Toxicity

Abstract: Hepatotoxicity associated with isoniazid and rifampicin is one of the major impediments in antituberculosis therapy. The present study explored the prophylactic and therapeutic efficacies of Spirulina maxima in isoniazid and rifampicin induced hepatic damage in a rat model. Hepatic damage induced in Wistar rats by isoniazid and rifampicin resulted in significant alterations in biomarkers of liver function, namely, bilirubin, aspartate transaminase, alanine transaminase, alkaline phosphatase, and oxidative stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Results from the present work show that liver function, histopathological features, and oxidative stress factors were significantly altered in RIF-and INH-treated rats, and the alteration was presented in a time-dependent manner, suggesting that the severity of liver injury induced by RIF and INH had close correlation with long-term drug usages (Pal et al, 2006). Coincided with our findings, the hepatotoxicity induced by RIF and INH administration was also observed and reported by other investigators (Jatav et al, 2014;Santhosh et al, 2006Santhosh et al, , 2007. Our results also showed that MAG treatment reversed the RIF-and INH-induced liver injuries, and the effect of high-dose MAG-treated group was superior to that of the low-dose-treated group, suggesting the protective effect of MAG on RIF-and INH-induced liver injuries.…”
Section: Discussionsupporting
confidence: 90%
“…Results from the present work show that liver function, histopathological features, and oxidative stress factors were significantly altered in RIF-and INH-treated rats, and the alteration was presented in a time-dependent manner, suggesting that the severity of liver injury induced by RIF and INH had close correlation with long-term drug usages (Pal et al, 2006). Coincided with our findings, the hepatotoxicity induced by RIF and INH administration was also observed and reported by other investigators (Jatav et al, 2014;Santhosh et al, 2006Santhosh et al, , 2007. Our results also showed that MAG treatment reversed the RIF-and INH-induced liver injuries, and the effect of high-dose MAG-treated group was superior to that of the low-dose-treated group, suggesting the protective effect of MAG on RIF-and INH-induced liver injuries.…”
Section: Discussionsupporting
confidence: 90%
“…The cell differentiation and antioxidant effects of these SACCS can be supported by various biological activity results using S. maxima . Several studies have reported that S. maxima affected the prevention of cardiomyoblasts in H9c2 cells, and protection of hepatic damage in a rat model 53 , 54 . Their effectiveness was based on strong antioxidants and various health care effects were found to be very similar to this study 55 , 56 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, animal studies indicated that vegetable extract can alleviate xenobiotic-induced hepatic damage (23,24). Several plant-derived extracts have been shown to relieve tuberculosisdrug-induced liver injury including Spirulina maxima, Crocus sativus, Ficus religiosa, Mucuna pruriens, Cassia auriculata, and Ziziphus oenoplia (25)(26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%